Narrative desire and the Book of Ruth - Powell, Stephanie Day (London Oxford New York New Delhi Sydney Bloomsbury T&T Clark, 2018)
Narrative desire and the Book of Ruth -- Resistance: ambiguity and artistry in the Book of Ruth -- Rupture: Ruth and fried green tomatoes -- Reclamation: Ruth and oranges are not the only fruit -- Re-engagement: Ruth and Golem, the spirit of exile -- (Un)final gleanings
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Feminist criticism; Bible -- Criticism, interpretation, etc; Bible -- Feminist criticism; Bible; Bible